2016
DOI: 10.1002/adfm.201603179
|View full text |Cite
|
Sign up to set email alerts
|

Visible‐Light Excited Luminescent Thermometer Based on Single Lanthanide Organic Frameworks

Abstract: Isostructural lanthanide organic frameworks (Me2NH2)3[Ln3(FDC)4(NO3)4]·4H2O (Ln = Eu (1), Gd (2), Tb (3), H2FDC = 9‐fluorenone‐2,7‐dicarboxylic acid), synthesized under solvothermal conditions, feature a Ln‐O‐C rod‐packing 3D framework. Time‐resolved luminescence studies show that in 1 the energy difference between the H2FDC triplet excited state (17794 cm−1) and the 5D0 Eu3+ level (17241 cm−1) is small enough to allow a strong thermally activated ion‐to‐ligand back energy transfer. Whereas the emission of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
124
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 196 publications
(126 citation statements)
references
References 53 publications
1
124
0
1
Order By: Relevance
“…The introduction of suitable organic chromophoric ligands into Ln-MOFs may enhance their light absorption ability to increase the fluorescent emission of Ln 3+ ions by the so-called "antennae effect" 41 . Therefore, sensing metal ions/VOCs can be realized by tuning the energy transfer efficiency from "antennae" to Ln 3+ ions through host-guest interactions.…”
mentioning
confidence: 99%
“…The introduction of suitable organic chromophoric ligands into Ln-MOFs may enhance their light absorption ability to increase the fluorescent emission of Ln 3+ ions by the so-called "antennae effect" 41 . Therefore, sensing metal ions/VOCs can be realized by tuning the energy transfer efficiency from "antennae" to Ln 3+ ions through host-guest interactions.…”
mentioning
confidence: 99%
“…As a common example, thermal deactivation of the 5 D 0 electronic state of Eu 3+ ion reduces luminescence intensity as temperature increases. Li et al [62] reported a luminescence decrease of 5 D 0 → 7 F 2 in (Me 2 NH 2 ) 3 [Eu 3 (FDC) 4 (NO 3 ) 4 ]·4H 2 O when setting temperature in the range of 12-320 K (Figure 1), and revealed the underlying thermally activated energy transfer mechanism from Eu 3+ to ligand FDC 2− , which is also benefitting from the small energy difference between 5 D 0 level (17241 cm −1 ) of Eu 3+ and triplet excited state (17794 cm −1 ) of FDC 2− . Recently, several examples of the anomalous emission enhancement at increased temperatures have been reported in nanosized materials.…”
Section: Controlling the Temperaturementioning
confidence: 99%
“…b) Digital photographs of the compound under 365 nm excitation recorded at 12 and 300 K. Reproduced with permission [62]. b) Digital photographs of the compound under 365 nm excitation recorded at 12 and 300 K. Reproduced with permission [62].…”
mentioning
confidence: 99%
“…Taking account of the excellent optical properties such as large Stokes shifts and high color purity of lanthanide MOFs (LnMOFs), a great deal of important investigations on LnMOFs have been carried out. And then, their promising abilities in detecting temperature, metal ions, oxygen, explosives and polychlorizated benzenes with high sensitivity and selectivity have also been exploited successfully [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]. Ratiometric luminescent sensors can provide a self-calibrated analyte concentration readout, which is unaffected by fluctuations of sensor concentration and/or instrumental parameters.…”
mentioning
confidence: 99%
“…In 1-3, the face-sharing defective cubes-like Eu 4 O 6 metal-oxygen clusters as 8-connected nodes construct the body centered cubic topological network with a Schläfli symbol of 4 24 .6 4 . The unique luminescence feature gives 1 the ability to detect the Al 3+ ions by the ratiometric luminescent approach with slope of 18,502 mol L −1 .…”
mentioning
confidence: 99%